ECONOMIC ANALYSIS OF TRITICALE PRODUCTION: A CASE STUDY OF CORUM PROVINCE, TURKEY - Bektas KADAKOGLU; Bahri KARLI; Mevlüt GÜL; Arif ÖZUYGUR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study aims to determine the production costs and profitability of the farmers’ triticale production in Corum province. Because it is an important region in Turkey, Corum province was selected as the research area in triticale production. The study’s data were determined by the stratified random sampling method obtained by the questionnaire method from 53 farms producing triticale in the Sungurlu district of Corum province. The production data set includes data for the 2019 year. According to the research findings, the average production cost per decare was calculated to be 290.85 TRY. The share of variable costs was 58.55% within the production costs, and the share of fixed costs was 41.45%. It was determined that the unit sale price of triticale was 0.87 TRY. The gross production value (GPV) of triticale in the region was calculated as 356.44 TRY/da, gross profit 185.73 TRY/da, and net profit 65.16 TRY/da. The unit cost of triticale in the region was 0.84 TRY. The relative profit was determined as 1.22 unit. As a result of the research, as the triticale production areas increase, the fixed costs per decare increase, and the variable costs decrease. The profitability indicators per decare and kilogram sales price increased with the triticale groups’ with.